2007
DOI: 10.1038/nmat2038
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric superstructure formed in a block copolymer via phase separation

Abstract: Self-assembly of amphiphilic block copolymers into well-ordered structures has attracted significant interest over the past decade. An especially attractive application of block-copolymer self-assembly is the formation of isoporous membranes. A major problem in this process is the lack of sufficient long-range order and the difficulty of up-scaling due to the time-consuming preparation steps. Here, we report an innovative and simple method to prepare isoporous membranes with nanometre-sized pores. The combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
746
1
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 698 publications
(759 citation statements)
references
References 32 publications
7
746
1
5
Order By: Relevance
“…Later, the combination of the self-assembly of block copolymers and non-solvent induced phase separation (SNIPS) process allowed the preparation of isoporous membranes with high porosity and sharp molecular weight cut-off. In 2007, the first isoporous block copolymer membrane was reported to be cast from polystyrene-block-poly(4-vinylpyridine) (PS-b-P4VP) by utilizing the diblock copolymer self-assembly and non-solvent induced phase inversion process (SNIPS) [11]. Later on it was shown that different additives can support the membrane formation [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Later, the combination of the self-assembly of block copolymers and non-solvent induced phase separation (SNIPS) process allowed the preparation of isoporous membranes with high porosity and sharp molecular weight cut-off. In 2007, the first isoporous block copolymer membrane was reported to be cast from polystyrene-block-poly(4-vinylpyridine) (PS-b-P4VP) by utilizing the diblock copolymer self-assembly and non-solvent induced phase inversion process (SNIPS) [11]. Later on it was shown that different additives can support the membrane formation [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Such a thin SiN x membrane is known to be complicated and expensive to fabricate, and fragile under mechanical contact or moisture at ambient conditions. In parallel, a template-based bottom-up method is useful to create a free-standing membrane with nanoapertures integrated on a geometrical support by utilizing selfassembly of nano-particles 22 or block copolymers 23 . The ability to control the aperture shape or dimension, however, is potentially limited, restricting the widespread use of such a templatemediated approach.…”
mentioning
confidence: 99%
“…In the last decade, functional block copolymer filtration membranes attracted enormous attention because of their isoporous surface structure and capability for responsiveness stimulated by external triggers [34][35][36][37][38][39][40][41]. The most prominent and first block copolymer in this field is polystyrene-block-poly(4-vinylpyridine) (PS-b-P4VP), which revealed tremendous potential for water purification and separation processes [42][43][44][45][46]. Quite recently, we reported on the preparation of the amphiphilic block copolymer polystyrene-block-poly(2-hydroxyethyl methacrylate) (PS-b-PHEMA) for the formation of integral asymmetric porous membranes featuring a high water flux [47].…”
Section: Introductionmentioning
confidence: 99%